The association between team job crafting and work engagement among nurses: a prospective cohort study - Mako Iida; Asuka Sakuraya; Kazuhiro Watanabe; Kotaro Imamura; Utako Sawada; Hiroto Akiyama; Yu Komase; Yuki Miyamoto; Norito Kawakami (BMC Psychology, 2024)
Abstract Background Team-level job crafting has been put forward as a method to promote nurses' mental health. However, a longitudinal association is unclear. Therefore, the objective of this study was to investigate the association between team job crafting at baseline and work engagement, work performance, psychological distress, and intention to leave at three-month and six-month follow-ups among Japanese hospital nurses. Also, whether an increase in the team job crafting during 3 or 6 months was associated with an increase in the work engagement during 3 or 6 months of individual nurses was examined. Methods A multilevel prospective cohort study was conducted. Data were collected from nurses of five hospitals in Japan at baseline (T1) and follow-ups at 3-months (T2) and 6-months (T3). A total of 2,478 nurses were included. The team job crafting scale for nurses and its three subscales were measured for the independent variables. Ward-means were used as ward-level variables. The dependent variables were work engagement, work performance, psychological distress, and intention to leave. Hierarchical Linear Modeling (HLM) was used to examine the multilevel association. The study protocol was registered at the UMIN Clinical Trials Registry (ID = UMIN000047810) (May 22, 2022). Results A total of 460 nurses completed the T1 survey (response rate = 18.6%), and data from 391 nurses nested in 30 wards were included in the analyses. The intraclass correlation coefficients (ICCs) at T1 were 0.02 for work engagement and 0.07 for team job crafting. The HLM revealed that ward-level team job crafting at T1 was not significantly associated with work engagement, work performance, psychological distress, and intention to leave at T2 or T3. The ward-level change (T3-T1) of “crafting for the task considering the team’s growth” (subscale for team job crafting) was significantly and positively associated with the change (T3-T1) in work engagement. Conclusions Ward-level team job crafting at baseline did not predict nurses' work engagement, work performance, psychological distress, or intention to leave at a three-month or six-month follow-up. The impact of ward-level team job crafting may attenuate over several months.